PELUNASAN BEA METERAI ATAS DOKUMEN DI INDONESIA - Evie Rachmawati Nur Ariyanti (Jurnal ADIL, 2019)
The Law No. 13/1985 sets a tax on documents, which is called stamp duty. Itsdetailed and technical implementation is further described in GovernmentRegulation No. 24/2000 on the New Tariff for Stamp Duty and its Imposition Limitof Nominal Price. So far, many people are familiar with only one type of stamp:seal on receipts. In addition, many people are still uninformed about when it iscompulsory to stamp on their documents. Through juridical-normative approach,this research found out that there is another alternative to attaching stamps orseals to pay stamp duty on documents: either manual or digital franking machine.This means of repayment involves fixed procedures. The sealing or stamping itselfuses seals on receipts or tax collection letters. This ty,stmpingmeans of sealing isdone to documents used as evidence previously not payable on stamp duty andinsufficiently paid. This stipulation also applies to documents made in othercountries which are to be used in Indonesia.